Mapping QTL associated with agronomic traits in bread wheat (Triticum aestivum L.) - Elangovan, M; Dholakia, B B; Rai, R; Lagu, M D; Tiwari, R; Gupta, R K; Gupta, V S (Journal of Cereal Research, 2011)
The major focus of global wheat research efforts is to identify loci governing important agronomic and quality related traits and to understand their complex interactions responsible for the end phenotype. The objective of this study was to identify Quantitative trait loci (QTL) for agronomic traits such as Sedimentation volume (Sv), Grain protein content (Gpc), Thousand grain weight (Tgw) and Test weight (Tw) which play an important role in determining the end use and marketability of wheat. To accomplish this task, an RIL population from a cross between two Indian wheat varieties â€œHI977â€ and â€œHD2329â€was used. The phenotypic data were collected from six environments including three different agro climatic zones for two consecutive years. Composite interval mapping revealed 68 QTL controlling Gpc, Sv, Tgw and Tw with individual phenotypic variation ranging from 7.0- 32.3% and total of 9 QTL clusters were detected on 7 chromosomes. AMMI model revealed significant contribution of G x E variance to all the traits. Furthermore, data analysis identified co-localization of few QTL affecting more than one trait.